Effects of Redox Homeostasis and Mitochondrial Damage on Alzheimer's Disease - Yi-Hsuan Wu; Hsi-Lung Hsieh (MDPI AG, 2023)
Bioenergetic mitochondrial dysfunction is a common feature of several diseases, including Alzheimer's disease (AD), where redox imbalance also plays an important role in terms of disease development. AD is an age-related disease and begins many years before the appearance of neurodegenerative symptoms. Intracellular tau aggregation, extracellular β-amyloid (Aβ) deposition in the brain, and even the APOE4 genotype contribute to the process of AD by impairing redox homeostasis and mitochondrial dysfunction. This review summarizes the evidence for the redox imbalance and mitochondrial dysfunction in AD and demonstrates the current therapeutic strategies related to mitochondrial maintenance.